Management of Fractured Endodontically Treated Tooth by Fibre Optic Composite Post-Core-Crown: A Case Report (Central Medical College Journal, 2022)
The restoration of endodontically treated tooth is a subject that has been evaluated and discussed widely in the dental literature. The goal of dental treatment is to provide optimal oral health, aesthetics and functions. The successful treatment of a badly broken endodontically treated tooth depends not only on the success of the endodontic treatment but also on good prosthetic reconstruction. The prosthetic treatment on a seriously damaged, endodontically treated tooth often requires an endodontic post as an additional retention element for core build up prior to crown restoration. This case report presents a male patient of 22 years of age with prosthetic crown fracture of endodontically treated maxillary left central incisor tooth. The following clinical case represents the clinical steps involved in the utilization of a fibre-reinforced composite post-core in a maxillary left central incisor and the subsequent treatment with a full veneer crown.Central Medical College Journal Vol 5 No 2 Jul 2021 PP 126-130